131k views
4 votes
3(-X+4)=7x-8. Yeahhhh...

3(-X+4)=7x-8. Yeahhhh...-example-1
User Newtrino
by
6.4k points

1 Answer

2 votes

Hey there!☺


Answer:\boxed{x=2}


Explanation:


3(-x+4)=7x-8

Let's start by simplifying both sides. First, we distribute.


(3)(-x)+(3)(4)=7x+-8


-3x+12=7x+-8


-3x+12=7x-8

Now let's subtract 7x from both sides.


-3x+12-7x=7x-8-7x\\-10x+12=-8

Now we will subtract 12 from both sides.


-10x+12-12=-8-12\\-10x=-20

In our last/final step, we will divide both sides by -10.


(-10x)/(-10)=(-20)/(-10)

Now simplify -20/-10.


-20/-10=2


x=2

Hope this helps!

User CarlosJavier
by
5.7k points